Wpływ różnych systemów opodatkowania dywidend w krajach Unii Europejskiej na wymaganą stopę zwrotu z akcji - Słoński, Tomasz (The Impact of Taxation System in EU Countries on Required Rate of Return, 2007)
This paper starts with analyzing the impact of dividend taxation system on shareholder's required ate of return in EU countries. The required rate of return was estimated using the dividend discount »del and than it was compared with security market line estimation (CAPM model). The comparison of different rate of returns exacts further corrections especially under an imputation system. Consequently, a taxation system may influence the debt holder's income as well. Therefore, a benefit torn interest tax shield under different taxation systems changes the value of the firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 387-399